2016
DOI: 10.1063/1.4944536
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of the supersonic turbulent boundary layer subjected to concave curvature

Abstract: By employing the Nanoparticle-based Planar Laser Scattering method and the particle image velocimetry, structural responses of a Mach 2.95 turbulent boundary layer to two concave curvatures (radiuses are 113 mm and 350 mm, respectively) are experimentally investigated. Large scale vortices formed in the flat plate region are observed to break up into smaller ones immediately after they flow into the concave region. Larger curvature tends to introduce more immediate breakup of the vortices. Fractal analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 26 publications
1
12
0
1
Order By: Relevance
“…A streamwise increase of density brought by the compressive waves can be clearly seen. The streamwise variation of turbulent structures along the concave wall is similar to the flow-visualization results given by Wang & Wang (2016). In the concave region, the vortex structures appear to have smaller scales than those in the flat-plate region.…”
Section: Instantaneous Flow Structuressupporting
confidence: 81%
See 2 more Smart Citations
“…A streamwise increase of density brought by the compressive waves can be clearly seen. The streamwise variation of turbulent structures along the concave wall is similar to the flow-visualization results given by Wang & Wang (2016). In the concave region, the vortex structures appear to have smaller scales than those in the flat-plate region.…”
Section: Instantaneous Flow Structuressupporting
confidence: 81%
“…Instantaneous streamwise flow structures of a supersonic concave boundary layer. (Wang & Wang 2016) that the concave curvature greatly affects the turbulence structures, further experimental and numerical investigations into this reorganization in the supersonic flow regime is still required to reveal detailed turbulent flow. So far, most of the studies regarding the supersonic concave boundary layer are focused on the mean and statistical properties (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As measured in previous studies (Fernando & Smits (2006), Donovan et al (1994), Spina et al (1994), Flaherty & Austin (2013a), Wang et al (2016b)), the boundary layer thickness decreases on a concave wall and on a flat plate with adverse pressure gradient in a supersonic flow. In contrast to this, recent by nano-particle planar laser scattering visualizations of the instantaneous two-dimensional flow Wang & Wang (2016) observed that the concave boundary layer becomes thicker. From the velocity profiles in the previous section we see that in the present study the boundary layer is on average thinner on concave walls, as seen also in the instantaneous slice shown on figure 16c.…”
Section: Thermal Effectsmentioning
confidence: 81%
“…Several experiments have tried to visualize the flow structures of Görtler vortices, including Luca et al (1993) for a Mach 7 flow, Ciolkosz & Spina (2006) at low supersonic Mach numbers varying from 1.06 to 2.87 and Flaherty (2013) at Mach 5.12. Recently, Wang & Wang (2016) studied the response of turbulent structures in a Ma = 2.95 supersonic boundary layer to concave curvature experimentally and found that the large scale vortices formed in the flat plate region break down into smaller ones immediately after being convected into the concave region. Since only a 2D longitudinal slice was obtained, it was difficult to speculate about the 3D vortex structures on the concave walls.…”
Section: Introductionmentioning
confidence: 99%